2017
DOI: 10.3168/jds.2016-12280
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Automated detection of behavioral changes from respiratory disease in pre-weaned calves

Abstract: Group housing of calves can pose a challenge in identifying respiratory disease; therefore, it is necessary to develop tools that can identify these disease events. In this experiment, pre-weaned calves (n = 30) were housed in groups with an automatic calf feeder and were fitted with an accelerometer. Step activity, lying behaviors, and feeding behaviors were recorded to determine the effect of respiratory disease. All calves were health scored twice daily, and calves with respiratory scores ≥5 were diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 23 publications
(34 reference statements)
4
35
1
1
Order By: Relevance
“…Differences in feeding behavior among studies may relate to the pathogenesis of the disease. In other studies, calves were diagnosed with a range of illnesses, including gastrointestinal, respiratory, or a combination of these diseases (Borderas et al, 2009;Swartz et al, 2017), or other signs of disease such as arthritis, fever, dull calf syndrome, and so on (Svensson and Jensen, 2007). However, in those studies, samples were not taken to verify the pathogenesis of the diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in feeding behavior among studies may relate to the pathogenesis of the disease. In other studies, calves were diagnosed with a range of illnesses, including gastrointestinal, respiratory, or a combination of these diseases (Borderas et al, 2009;Swartz et al, 2017), or other signs of disease such as arthritis, fever, dull calf syndrome, and so on (Svensson and Jensen, 2007). However, in those studies, samples were not taken to verify the pathogenesis of the diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Once an animal displays clinical signs of NCD, much of the associated tissue damage to the intestinal submuscosa has already 8209 occurred (Schroeder et al, 2012); therefore, early detection of NCD would enable calves to be promptly treated and moved to sick pens thereby reducing tissue damage and risk of disease transmission to other calves. Previous studies using ACFS and accelerometers have reported changes in feeding (Svensson and Jensen, 2007;Borderas et al, 2009;Lowe et al, 2016) and lying behavior (Swartz et al, 2017) in response to NCD and respiratory disease. However, those studies predominantly focused on changes in behavior once calves became clinically ill or the time period just prior (Svensson and Jensen, 2007;Borderas et al, 2009), or calves that were diagnosed with respiratory disease (Swartz et al, 2017).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Reduced feed intake is often an early sign of disease (Johnson, 2002) that can now be continuously monitored using precision dairy management technologies. For example, it has been reported that calves reduce milk intake at the day of respiratory disease diagnosis (Swartz et al, 2017) and that cows present reduced DMI in the first 2 wk of lactation before the diagnosis of metritis (Huzzey et al, 2007;Schirmann et al, 2016). Therefore, the objective of this experiment was to investigate the association between tick-borne disease and feeding and drinking behavior (total daily intake, frequency of visits, and total duration of visits) of weaned calves relative to weekly disease detection routine.…”
Section: Short Communicationmentioning
confidence: 99%
“…Infrared thermography has also been used to investigate how temperature changes at different anatomical areas relate to the onset of BVD (Schaefer et al, 2004) and differences in feed efficiency (Montanholi et al, 2009(Montanholi et al, , 2010Martello et al, 2016). Moreover, changes in feeding behaviors, measured using automated calf feeders, have been used to assess disease in calves (Svensson and Jensen, 2007;Borderas et al, 2009;Swartz et al, 2017;Sutherland et al, 2018). Automated calf feeders are able to record information, including milk consumption, visit duration, and the number of rewarded (calf receives an allocation of milk) and unrewarded (calf does not receive an allocation of milk) visits calves make to the feeder.…”
Section: Introductionmentioning
confidence: 99%